International Conference on Photonics 2010 2010
DOI: 10.1109/icp.2010.5604404
|View full text |Cite
|
Sign up to set email alerts
|

Influence of immerse time on the properties of zinc oxide nanostructures

Abstract: Zinc oxide (ZnO) is an emerging optoelectronic material in large area electronic applications due to its various functional behaviors. We present the fabrication and characterizations of ZnO nanostructures. The ZnO nanostructures consisting of nanorods were synthesized using sol-gel hydrothermal technique on oxidized silicon (Si) substrates. In the fabrication of ZnO nanorods, the oxidized Si substrates were immersed in ZnO aqueous solution for different times ranging from 3.5 hours to 5 hours. The surface mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The cracks in the films deposited on glass may be attributed to an uncompleted reaction. Many authors have investigated the surface morphology of ZnO thin films obtained by different methods and deposited onto various substrates in the literature [29][30][31][32][33].…”
Section: Morphological Propertiesmentioning
confidence: 99%
“…The cracks in the films deposited on glass may be attributed to an uncompleted reaction. Many authors have investigated the surface morphology of ZnO thin films obtained by different methods and deposited onto various substrates in the literature [29][30][31][32][33].…”
Section: Morphological Propertiesmentioning
confidence: 99%
“…One of the most versatile and studied metal oxide material is the zinc oxide (ZnO), which exhibits the excellent physical, chemical, electrical, optoelectronic properties and piezoelectric dual properties. Thus, they are highly suitable for a diverse application (11)(12)(13)(14). One-dimensional (1D) Zinc oxide (ZnO) which have a direct wide band gap (3.37eV) semiconductor with a large excitation binding energy (60 meV) at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…results in bigger grains and the surface roughness area increases with the increasing precursor concentration. Ilican et al [13] studied the effect of chuck speed between 3000 and 5000 rpm for the preparation of thin films, which was concluded that greater the chuck speed lower was the grain size of the crystallite. The texture coefficient decreased with increase in chuck rotation.…”
Section: Introductionmentioning
confidence: 99%